Exploring a Gene Panel for Parkinson’s Disease in an Egyptian Cohort - Gabr, Asmaa Saeed (AUC Knowledge Fountain, 2024)
Parkinson’s disease is a highly heterogeneous disorder characterized by diverse neuropathological features, clinical presentations and progression patterns. In Egypt, Parkinson’s disease incidence rates lie outside the range reported elsewhere. The genetic background to the pathogenesis of Parkinson's disease has been postulated for a long time. However, Parkinson’s disease has never been systematically investigated in Egypt. This study aimed to explore genetic variants and interactions that are associated with the familial and sporadic forms of Parkinson's disease in an Egyptian cohort. This includes examining variants in PD-related genes, exploring the role of specific genes like MAPT and adjacent genomic regions, and investigating the combined effects between genes such as APOE and BCHE. Whole exome sequencing was conducted for individuals with a family history of PD. Identified variants were filtered for rarity and potential pathogenicity. Notable findings included variants in LRRK2, GBA, DNAJC6, DLG2, SYNJ1, PITRM1 and others. The PITRM1 R892K variant, identified in multiple family members, showed incomplete and age-related penetrance. Furthermore, investigating the association between genetic variants in MAPT, KANSL1 and SPPL2C genes and the risk of developing PD did not find statistically significant associations between the studied variants and PD risk. Similarly, the APOE and BCHE variants did not show a strong association with PD risk, and the association was statistically non-significant. The studied variants showcased varying correlations with the clinical outcomes, and the BCHE K-variant demonstrated a statistically significant correlation with the severity of Parkinson's disease symptoms as measured by the UPDRS. Additionally, the analysis revealed a series of SNP-SNP interactions that were significantly associated with a lower risk of PD. These findings are a piece of the larger puzzle in understanding the genetics of PD and underscore the importance of considering multiple genetic factors rather than single genetic variants.